ChemInform Abstract: Spin‐Echo Electron Paramagnetic Resonance (EPR) Spectroscopy of a Pore‐Forming (Lipo)Peptaibol in Model and Bacterial Membranes. Issue 29 (1st July 2013) - Dzuba, Sergei A.; Raap, Jan
Abstract Review: 66 refs.